Fuzzy Ponics: a Fuzzy Based System to Control Temperature, Relative Humidity, Electrical Conductivity and PH of Hydroponics - E. Pakzad, Armie; Ali Pakzad, Abbas (International Journal of Engineering and Technology, 2018)
Hydroponics is a process in which plants grow in a nutrient solution instead of soil. It is a controlled environment agriculture (CEA), which needs intensive controlling of the greenhouse environmental condition such as temperature and relative humidity (RH) along with electrical conductivity (EC) and pH of nutrient solution. A successful Hydroponics System (HS) depends on the way the greenhouse is maintained in terms of the environmental condition and the plantâ€™s nutrient uptake. This paper presents FuzzyPonics, a system which focuses on the application of fuzzy logic algorithm to automatically control the temperature and RH of the greenhouse, alongside EC and pH of the nutrient solution. The identified input parameters were classified accordingly, relative to predefined linguistic outputs and solutions. Sugeno-style of Fuzzy Inference System (FIS) and triangular membership functions were used. The results were simulated using the rule viewer of Matlab Fuzzy Logic Toolbox for six FIS and the proponents were able to get favorable results, which only showed that a fuzzy logic controller is a powerful tool to control the environmental condition and the nutrient solutionâ€™s pH and EC of a hydroponics system. Â Â Â Â